KnowVolution of a Fungal Laccase toward Alkaline pH. (15th April 2019) - Novoa, Catalina; Dhoke, Gaurao V.; Mate, Diana M.; Martínez, Ronny; Haarmann, Thomas; Schreiter, Martina; Eidner, Jasmin; Schwerdtfeger, Ruth; Lorenz, Patrick; Davari, Mehdi D.; Jakob, Felix; Schwaneberg, Ulrich
Abstract: To date, commercial laccase preparations are used in the food, textile, and paper and pulp industries (mild pH). Laccases are attractive in the synthesis of dye molecules or oxidative lignin treatment, which take place at high pH (≥8.0). So far, one fungal laccase has been reported to be active at alkaline pH. Herein, engineering of the fungal laccase from Melanocarpus albomyces (MaL) for increased activity toward the substrate 2, 6‐dimethoxyphenol at pH (≥9.0) is reported. Through a knowledge‐gaining directed evolution (KnowVolution) campaign, the key positions Leu365 and Leu513 were identified to increase alkaline tolerance. Both positions are located in close proximity of the T1Cu site. Molecular docking and simulations studies reveal that both substitutions act in a synergic way to stabilize and improve laccase activity at higher pH. Kinetic characterization of the final variant MaL‐M1 (L365E/L513M) revealed at pH 9.8 a threefold improved k cat ( k cat =(6.0±0.2) s −1 ) compared with that of wild‐type M. albomyces laccase ( k cat =(2.11±0.07) s −1 ). Abstract : Evolving tolerance : One single round of KnowVolution yields the engineered fungal laccase from Melanocarpus albomyces (MaL) with a threefold improved k cat at pH 9.8. Structural rearrangement surrounding the T1Cu site is key to improve the alkaline pH (≥9.0) tolerance of laccase.